2021
DOI: 10.7717/peerj.12694
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity and potential risk factors associated with Salmonella contamination of seafood products sold in retail markets in Bangkok, Thailand

Abstract: Consumption of contaminated food causes 600 million cases, including 420,000 of fatal infections every year. Estimated cost from food-borne illnesses is USD 110 billion per year, which is an economic burden to low- and middle-income countries. Thailand is a leading producer and consumer of seafood, but little is known about bacterial contamination in seafood. In particular, public health agencies need to know the relationship between Salmonella contamination in seafood and risk factors, as assessed with readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
15
1
3
Order By: Relevance
“…and Vibrio spp. in various kinds of bivalve molluscs was observed by Hariharan and Amadi [ 15 ] and Atwill and Jeamsripong [ 52 ]. The latter authors noticed that the contamination of shellfish with Salmonella spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…and Vibrio spp. in various kinds of bivalve molluscs was observed by Hariharan and Amadi [ 15 ] and Atwill and Jeamsripong [ 52 ]. The latter authors noticed that the contamination of shellfish with Salmonella spp.…”
Section: Discussionmentioning
confidence: 95%
“…was significantly associated with the type and source of molluscs, their sampling location, and the presence of E. coli and Vibrio spp. [ 52 ]. In the current study, it was also found that the presence of more than one pathogen was mainly identified in clams and mussels harvested in the Netherlands ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…es parte natural de los camarones, por lo que su presencia es más probable [16], no obstante en México no está permitido. Otros autores mencionan que la principal causa de contaminación de Salmonella es debida a que está presente en los sistemas acuícolas pero también influye las instalaciones y la prácticas de higiene durante el transporte, almacenamiento y manipulación [18].…”
Section: Discussionunclassified
“…En Tailandia realizaron un estudio en camarones encontrando Salmonella spp. y E. coli en del cual fue 47% y 100% respectivamente [18], referente a E. coli se mostró el mismo comportamiento que en este estudio. También menciona que para este microorganismo el hielo es un factor de riesgo debido a que está contaminado lo que es considerado como un vehículo ya que el hielo al derretirse puede propagar las bacterias [18].…”
Section: Discussionunclassified
See 1 more Smart Citation